When China rules the world the rise of the Middle Kingdom and the end of the Western world - Jacques, Martin (Allen Lane, 2009)
For well over two hundred years we have lived in a western-made world, one where the very notion of being modern is inextricably bound up with being western. The twenty-first century will be different. The rise of China, India and the Asian tigers means that, for the first time, modernity will no longer be exclusively western. The west will be confronted with the fact that its systems, institutions and values are no longer the only ones on offer. The key idea of Martin Jacques's ground-breaking new book is that we are moving into an era of contested modernity. The central player in this new world will be China. Continental in size and mentality, China is a 'civilisation-state' whose characteristics, attitudes and values long predate its existence as a nation-state. Although clearly influenced by the west, its extraordinary size and history mean that it will remain highly distinct, and as it exercises its rapidly growing power it will change much more than the world's geo-politics. The nation-state as we understand it will no longer be globally dominant, and the Westphalian state-system will be transformed; ideas of race will be redrawn. This profound and far-sighted book explains for the first time the deeper meaning of the rise of China.